Bactericidal thurincin H causes unique morphological changes in Bacillus cereus F4552 without affecting membrane permeability. Issue 1 (30th June 2014) - Wang, Gaoyan; Feng, Guoping; Snyder, Abigail B.; Manns, David C.; Churey, John. J.; Worobo, Randy W.
Abstract Thurincin H is an antilisterial bacteriocin produced by Bacillus thuringiensis SF361. It exhibits inhibitory activity against a wide range of Gram‐positive foodborne pathogens and spoilage bacteria including Listeria monocytogenes, B. cereus, and B. subtilis. This hydrophobic, anionic bacteriocin folds into a hairpin structure maintained by four pairs of unique sulfur to α‐carbon thioether bonds. As its hydrophobicity and structure are quite different from most archived bacteriocins, this study aimed to elucidate its mode of action and compare it with the mechanisms of other well‐characterized bacteriocins. The results indicated that, although bactericidal to B. cereus F4552, thurincin H did not lead to optical density reduction or detectable changes in cell membrane permeability. B. cereus F4552 imaged by scanning electron microscopy after treatment with thurincin H at 32 × MIC showed regular rod‐shaped cells, while only cells treated with thurincin H at the elevated levels of 256 × MIC showed loss of cell integrity and rigidity. Both concentrations caused greater than 99% of cell viability reduction. In contrast, nisin caused significant cell membrane permeability at concentration as low as 2 × MIC. These results indicated a difference in the mode of action for thurincin H compared with the generalized pore‐forming mechanism of many lantibiotics, such as nisin.